Cortical thinning is associated with disease stages and dementia in Parkinson's disease. Issue 8 (5th March 2013) - Zarei, Mojtaba; Ibarretxe-Bilbao, Naroa; Compta, Yaroslau; Hough, Morgan; Junque, Carme; Bargallo, Nuria; Tolosa, Eduardo; Martí, Maria Jose
Abstract : Objective: To investigate the pattern of cortical thinning in Parkinson's disease (PD) across different disease stages and to elucidate to what extent cortical thinning is related to cognitive impairment. Design: Ninety-six subjects including 39 controls and 57 PD patients participated in this study. PD subjects were divided into three groups (early, n=24; moderate, n=18; with dementia, n=15). High field structural brain MRI images were acquired in a 3T scanner and analyses of cortical thickness and surface were carried out. Vertex-wise group comparisons were performed and cortical thickness was correlated with motor and cognitive measures. Results: We found a positive correlation between Mini-Mental State Examination scores and cortical thickness in the anterior temporal, dorsolateral prefrontal, posterior cingulate, temporal fusiform and occipitotemporal cortex. Unified Parkinson's Disease Rating Scale-III (motor subsection) scores showed a robust negative correlation with caudate volumes. We found that disease stage in PD was associated with thinning of the medial frontal (premotor and supplementary motor cortex), posterior cingulate, precuneus, lateral occipital, temporal and dorsolateral prefrontal cortex. Discriminant analysis and a receiver operating characteristics approach showed that mean cortical thickness and hippocampus volume have 80% accuracy in identifying PD patients with dementia. PD stage and PD dementia can be characterised by a specific pattern of cortical thinning. Conclusions: We conclude that measuring cortical thickness can be useful in assessing disease stage and cognitive impairment in patients with PD. In addition, cortical thickness may be useful in identifying dementia in PD.